DFT insights into the detection of NH 3 , CO, and SO 2 gases by the penta-PtSiTe monolayer - Martins, Nicolas F. [UNESP]; Laranjeira, José A.S. [UNESP]; Bezzerga, Djamel; Haidar, El-Abed; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
This study investigates the penta-PtSiTe monolayer as an efficient sensor for toxic gases (NH 3 , CO, and SO 2 ), highlighting its promising performance through density functional theory (DFT) simulations. For all three gases, the monolayer demonstrates strong chemisorption, with adsorption energies of −1.10 eV (NH 3 ), −0.59 eV (CO), and −1.07 eV (SO 2 ), indicating robust interactions with the substrate. Regarding its electronic response, the adsorption of NH 3 , CO and SO 2 decreases the material’s band gap by 0.18 eV, 0.15 eV, and 0.37 eV, respectively, suggesting a high sensitivity of the penta-PtSiTe sensor. The work function (WF) analysis further supports this, as the pristine monolayer has a WF of 4.79 eV, which decreases to 4.44 eV (NH 3 ), 4.76 eV (CO), and 4.69 eV (SO 2 ), reflecting a strong electronic affinity between the monolayer and all the molecules. Additionally, the monolayer exhibits rapid recovery times for gas desorption, especially at elevated temperatures, making it ideal for reusable sensor applications.